(untitled) (Terr@ Plural, 2023)
Due to the cold climate and altitude, to identify trends in the dynamic vegetation and the main factors that contribute to changes in vegetation cover in grassland areas is essential to understand climate change in mountainous regions. Landsat-8 OLI and Landsat-1 MSS images from 1973 to 2022 of Morraria do Urucum and Serra do Amolar were pre-processed in the GEE cloud platform and QGIS. The resampling method per pixel in the scale of values defined for vegetation Campos de Altitude was used to show changes in vegetation cover and its dynamics through the NDVI index. In both study areas, a continuous trend of significant reduction of vegetation in highland grasslands was observed over 50 years. The average decrease was 49% for Urucum (less 2,164 hectares) and 43% for Amolar (less 3,959 hectares). The use of GHG to obtain remote sensing data combined with temporal image analysis offers the potential to quickly perceive trends in large- and small-scale vegetation cover change.